Nanostructure characterization of soot particles from biodiesel and diesel spray flame in a constant volume combustion chamber. (1st January 2019) - Hirner, Felix Sebastian; Hwang, Joonsik; Bae, Choongsik; Patel, Chetankumar; Gupta, Tarun; Agarwal, Avinash Kumar
Highlights: Regardless of fuel, primary particle diameter was decreased as the injection pressure increased. Primary particle diameter of biodiesel fuels was 1–2 nm smaller than that of diesel. Biodiesel primary particles were consisted of lower fringe tortuosity and spacing layers. Shorter fringe length in combination with lower tortuosity led to the smallest fringe spacing. Abstract: This study investigates the effect of biodiesel fuels on morphological characteristics of soot particles from spray flame in a constant volume combustion chamber. The experiments were carried out under simulated diesel engine condition. The auto-ignition of injected fuel was carried out at an ambient pressure of 5 MPa and ambient temperature of 978.15 K. The soot particles were captured with a transmission electron microscope (TEM) grid inside the flame by thermophoretic effect. They were characterized as primary particle diameter, graphene layer (fringe) length, fringe tortuosity, and fringe spacing based on the image processing from original TEM image. Three different kinds of biodiesel fuels, waste cooking oil biodiesel, Jatropha biodiesel and Karanja biodiesel were used in the test. Conventional diesel fuel was utilized as a baseline fuel for the comparison. The tested fuels were injected with injection pressures of 40, 80, and 120 MPa by means of common-rail injection system. The experimental result showed that all of the biodiesel fuels had smaller primary particle diameter than that of conventional diesel regardless of injection pressures. The soot particles from biodiesel fuels were also distinguished showing characteristically shorter fringe length and lower tortuosity. These experiments unveiled a correlation between the nano-structural parameters for the early stage of oxidation inside the flame.